`int (13 - x) dx` Find the indefinite integral.

Textbook Question

Chapter 4, 4.1 - Problem 12 - Calculus of a Single Variable (10th Edition, Ron Larson).
See all solutions for this textbook.

1 Answer | Add Yours

sciencesolve's profile pic

sciencesolve | Teacher | (Level 3) Educator Emeritus

Posted on

You need to evaluate the indefinite integral, hence, you need to split the integral, such that:

`int (13 - x) dx = int 13 dx - int x dx`

You need to use the following formula `int x^n dx = (x^(n+1))/(n+1) + c`

Replacing 1 for n yields:

`int x^1 dx = (x^(1+1))/(1 +1) + c`

`int x^1 dx = (x^2)/2 + c`

`int (13 - x) dx = 13x - (x^2)/2 + c`

Hence, evaluating the indefinite integral, yields `int (13 - x) dx = 13x - (x^2)/2 + c.`

We’ve answered 318,982 questions. We can answer yours, too.

Ask a question